EEKSISTENSI TRADISI MELEPAS AYAM PADA PERKAWINAN ADAT JAWA : PERSPEKTIF HUKUM ISLAM: Studi Desa Bedahlawak Kecamatan Tembelang Kabupaten Jombang - Nafs, Laila Shafa'un; Afif, Abdullah (SHAKHSIYAH BURHANIYAH: Jurnal Penelitian Hukum Islam, 2024)
One of the Javanese traditional wedding ceremonies that we can still see in the village of Bedahlawak, Tembelang District, Jombang Regency, is the tradition of releasing chicken during a Javanese wedding. This research aims to understand the implementation of the tradition of releasing a chicken in Javanese traditional weddings in the village of Bedahlawak, as well as the muslim community’s views on this tradition and its connection to Islamic law. Through qualitative field research with a socio legal approach, using primary data collection techniques from the field such as observation, interviews, and documentation, as well as secondary data. The process of implementing this tradition takes place during the bridal entourage, where the bride’s and groom’s house are separated by a large river. Implementing this tradiyion is relatively short, starting with the recitation of prayers, and before crossing the bridge over the river, the chicken will be released on the bridge’s edge. There are people who continue to practice and those who abandon this tradition. Variations have also been found. If the tradition is performed with the intention of seeking help from someone other than Allah SWT, it can be considered as a forbidden practice ( haram ) and a corrupt tradition ( urf’ fasid ) . However, if the intention is good and only seeks safety from Allah SWT without any conflicting intentions, then it is considered a practice in accordance with Islamic law and a valid tradition ( urf shahih).